CryoEM analysis of small plant biocatalysts at sub‐2 Å resolution. Issue 1 (23rd December 2021) - Dimos, Nicole; Helmer, Carl P. O.; Chánique, Andrea M.; Wahl, Markus C.; Kourist, Robert; Hilal, Tarek; Loll, Bernhard
Abstract : Although cryo‐electron microscopy has revolutionized structural biology, its applicability to high‐resolution structural analysis of comparatively small enzymes so far remains largely unexplored. Here, two cryo‐EM structures of plant borneol dehydrogenases of ∼120 kDa at or below 2 Å resolution are reported. Abstract : Enzyme catalysis has emerged as a key technology for developing efficient, sustainable processes in the chemical, biotechnological and pharmaceutical industries. Plants provide large and diverse pools of biosynthetic enzymes that facilitate complex reactions, such as the formation of intricate terpene carbon skeletons, with exquisite specificity. High‐resolution structural analysis of these enzymes is crucial in order to understand their mechanisms and modulate their properties by targeted engineering. Although cryo‐electron microscopy (cryoEM) has revolutionized structural biology, its applicability to high‐resolution structural analysis of comparatively small enzymes has so far been largely unexplored. Here, it is shown that cryoEM can reveal the structures of plant borneol dehydrogenases of ∼120 kDa at or below 2 Å resolution, paving the way for the rapid development of new biocatalysts that can provide access to bioactive terpenes and terpenoids.